Colonial gulag: the populating of the Port Macquarie penal settlement, 1821-1832 - Roberts, David Andrew (History Australia, 2017)
Recent developments in convict and penal studies are placing that field at the forefront of the ‘digital humanities’. In that vein, this article employs some newly digitised records relating to the Port Macquarie penal settlement in the 1820s to rectify the neglect of that settlement in the historical literature. The rise and fall of the colonial penal settlements involved monumental and rapid population movements that were meticulously documented by the colonial authorities. Nevertheless, despite some key works in recent years, there exists a rather meagre understanding of the processes by which the penal settlements were populated, and of the composition and status of their populations. In this article I demonstrate how data extracted from the bureaucratic infrastructure of convict management can be analysed to reveal some fundamental trends and particulars concerning the demography of the Port Macquarie population, and to reveal the various means, terms and conditions under which they were sent. It is hoped that this study might platform future re-evaluations of the history of that settlement, and of the colonial penal settlement system more broadly.